10 years of the Narradores da Maré Extension Project: Extension pedagogical practices with native peoples and traditional communities of Espírito Santo. - Gonzalez, Soler; Teixeira Ramos, Andreia (Guará Journal, 2025)
This article presents extension actions carried out by the Narradores da Maré Extension Project in partnership with the research group Territories of Autopoietic Learning/CNPq, created in 2014. Both have and with pedagogical practices that articulate research, extension, teaching and teacher training in Environmental Education, involving students and teachers of undergraduate, graduate, basic education, fishermen, crab shredders, crab pickers, potters, congueiros and indigenous Tupinikim and Guarani of Espírito Santo. The theoretical and methodological approaches dialogue with the studies with everyday life, with the narrative research and the perspective of education of Paulo Freire, and with the Education for Ethnic-Racial Relations. As a result, we listed published articles, field classes, Cineconversations workshop, Podcast episodes, online lives, the I Research, Extension and Teaching Seminar in educational networks with other ecologies and the realization of I, II, III and IV Unsubmissive Ecologies. With the actions carried out, the products and educational content created and the results disseminated on social networks, the Narradores da Maré project affirms the commitment to a counter-colonial, anti-racist Environmental Education and as a practice of freedom, supported by Laws 10.639/2003 and 11.645/2008.